2023
DOI: 10.1111/brv.12954
|View full text |Cite
|
Sign up to set email alerts
|

Social learning in non‐grouping animals

Abstract: Social learning is widespread in the animal kingdom and is involved in behaviours from navigation and predator avoidance to mate choice and foraging. While social learning has been extensively studied in group-living species, this article presents a literature review demonstrating that social learning is also seen in a range of non-grouping animals, including arthropods, fishes and tetrapod groups, and in a variety of behavioural contexts. We should not be surprised by this pattern, since non-grouping animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…Butterfly population dynamics depend on the abundance of host plants, and butterfly decline in Europe is most pronounced for habitat specialists or sedentary species that depend on host plants or habitats most susceptible to regression (Habel et al 2016;Seibold et al 2019). Furthermore, recent research has revealed that some butterfly behaviors depend on the presence of social cues (Nieberding et al 2021;Webster 2023; but see Aikins, Altizer, and Sasaki 2023), for example during sexual interactions (Dion et al 2019).…”
Section: Pagementioning
confidence: 99%
“…Butterfly population dynamics depend on the abundance of host plants, and butterfly decline in Europe is most pronounced for habitat specialists or sedentary species that depend on host plants or habitats most susceptible to regression (Habel et al 2016;Seibold et al 2019). Furthermore, recent research has revealed that some butterfly behaviors depend on the presence of social cues (Nieberding et al 2021;Webster 2023; but see Aikins, Altizer, and Sasaki 2023), for example during sexual interactions (Dion et al 2019).…”
Section: Pagementioning
confidence: 99%